Molecular characterization of doxorubicin resistance and cancer stem cells in a canine mammary adenocarcinoma cell line - Sahabi, Kabiru (2018)
Canine mammary gland tumour (CMT) is the commonest neoplasm affecting the female dog, with a prevalence of 39% in Malaysian female dogs. Metastasis to the lung is a common cause of death in the affected dogs. Cancer stem cells (CSCs) are small proportion of cancer cells that are able to initiate tumours, metastasis and facilitate recurrence due to properties such as self-renew, longevity, resistance to radiotherapy and chemotherapy, undergo a dormant state, ability to differentiate and evade apoptosis. Drug resistance in cancer cells, either acquired or inherent is a major cause of failure of many forms of anti-cancer chemotherapy mostly due to the expression of drug efflux genes called ATP-binding cassettes (ABC) and other factors. MicroRNAs (miRNA) are short non-coding RNA that can inhibit the translation of messenger RNA (mRNA) to protein in multicellular organisms; where majority of mRNAs are predicted to be under the control of miRNA. The objective of this study was to develop a doxorubicin resistant CMT cell line and determine its in vitro and in vivo (tumour induction capabilities in mouse models) characteristics, and to isolate and characterize (mRNA expression and miRNA transcription) CSCs from the cell line and its doxorubicin-sensitive original cells. Doxorubicin-resistant CMT-Star cells were developed from CMT-Stylo cells by exposing the cells to increasing concentrations of doxorubicin from 10 nM to 100 nM over 5 months. In vitro characterization was performed using the MTT assay, anchorage independent growth, AO/PI assays; and in vivo tumorigenic and metastatic properties in NOD/SCID mouse models. Quantitative real-time PCR (QPCR) was used to evaluate the expression of selected drug resistant genes in CMT-Star cells. Allophycocyanin conjugated CD44 and R-Phycoerythrin conjugated CD24 antibodies were used to sort putative CSC from the 2 cell lines. QPCR was used to determine the expression of stem cell marker aldehyde dehydrogenase in the sorted cells. Gene expression profiling of the two cell lines and sorted CSC was done using a 44K canine specific gene expression microarray by Agilent Technologies®. The miRNA profiling was done using Agilent SurePrint® custom canine specific miRNA platform. Signalling pathways, biological and cellular processes involved in drug resistance and CSC was explored using GeneSpring® and Database for Annotation, Visualization and Integrated Discovery (DAVID). Hierarchical clustering was performed on the gene expression profiles and Venn diagrams used to show overlapping genes in the datasets. The expressions of ABCB1 and ABCG2 were significantly increased in CMT-Star cell line. Both cell lines developed tumours in NOD/SCID mice. The expression of 785 genes and 14 miRNAs were altered in CMT-Star cells. Downregulating Plasminogen (PLG), plasminogen activator urokinase (PLAU); while upregulating transforming growth factor beta receptor 3 (TGFβR3) and ABCB1 makes CMT-Star cells less proliferative, less invasive and more resistant to chemotherapeutic drugs. The expression of 309 genes and 6 miRNAs were altered in CMT-Stylo CSC, while the expression of 206 genes and 14 miRNAs were altered in CMT-Star CSC. The upregulation of TGFβR 3, IL-6, nuclear receptor subfamily 4, Wnt Signalling, EGFR1 Signalling were observed in the two CSC populations, making the CSC in this study quiescent, self-renewing, tumour initiating, able to avoid detection by the immune system and drug resistant. Novel miRNAs, yet to be characterized in cancer were also identified with changes in transcription in various comparisons that are yet to be explored. In conclusion, this study has profiled the miRNA transcription and mRNA expression in the sub population of cells with CSC marker expression from canine mammary adenocarcinoma cells. The identified miRNAs and mRNAs regulate factors and pathways that maintain the doxorubicin resistant and CSC phenotypes, and require further research to investigate their potentials as therapeutic targets to facilitate development of new therapeutic strategies based on these novel miRNA and mRNA targets.